KEPEMIMPINAN LURAH DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR LURAH RAHANDOUNA KECAMATAN POASIA KOTA KENDARI - Sukadi; Muhammad Ihsan Mattalitti; Darwan Sari; La Ode Abdul Harlan; Wahyuddin; Abdul Rahman (Journal Publicuho, 2024)
This study aims to analyze the leadership style of the Rahandouna Village Head in supporting the improvement of employee performance at the Rahandouna Village Office, Poasia District, Kendari City. The focus of the research is directed at four leadership indicators, namely as innovators, communicators, motivators, and controllers. The research method used is qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that the role of the Rahandouna Village Head as an innovator is not optimal. The lack of new ideas and innovations hinders improving creativity and work efficiency. On the contrary, as a communicator, the village head shows good communication skills, creating a harmonious and conducive working atmosphere. In the motivator aspect, the village head consistently encourages, and guidance, and emphasizes the importance of discipline, which supports the improvement of employee morale. However, in its role as a controller, the village head has not been effective, characterized by low supervision of employee performance and attendance, which harms work discipline.